Adversity Quotient Dictates Critical Thinking And Information Processing In Nonroutine Mathematics: Adversity Quotient Menentukan Berpikir Kritis Dan Pemrosesan Informasi Pada Matematika Nonrutin - Mardiyah Mardiyah; Kamid Kamid; Rohati Rohati (Academia Open, 2026)
General Background Modern education requires analytical reasoning skills to evaluate evidence, formulate logical decisions, and solve complex educational challenges. Specific Background Successfully resolving unconventional numerical problems demands persistent cognitive effort, which relies heavily on a student's psychological endurance and their sequential cognitive stages. Knowledge Gap While previous research connects resilience to problem-solving, literature lacks a comprehensive mapping of how different endurance categories specifically govern the sequential stages of encoding, storage, retrieval, and monitoring during complex cognitive tasks. Aims This qualitative descriptive study examines analytical abilities across three psychological endurance categories in solving unconventional numerical tasks, viewed through the lens of cognitive sequential stages. Results Data from eighth-grade students reveal that highly resilient climbers optimally execute all analytical indicators alongside flawless cognitive sequencing. Moderate-endurance campers demonstrate adequate initial understanding but exhibit inconsistencies during the evaluation and monitoring phases. Conversely, low-resilience quitters display severe reasoning deficiencies, particularly struggling with encoding initial contexts and reflecting on potential solutions. Novelty This research distinctly maps psychological endurance categories directly onto cognitive mechanics, proving that mental tenacity fundamentally dictates the structural quality of logical reasoning. Implications Educational practitioners must tailor instructional scaffolding according to student psychological resilience to strengthen cognitive sequencing and overall reasoning capabilities. Highlights High psychological resilience guarantees optimal cognitive encoding and meticulous strategic evaluation. Moderate endurance leads to adequate problem comprehension but highly inconsistent solution monitoring. Low tenacity causes severe difficulties in understanding initial concepts and formulating logical reasoning. Keywords Adversity Quotient; Critical Thinking; Information Processing; Nonroutine Problems; Cognitive Resilience